The stress–strain behavior of WC-Co hardmetals - Golovchan, V.T.; Litoshenko, N.V. (Computational materials science, 2010)
The calculating algorithm for construction of the stress–strain curves of WC-Co hardmetals in simple tension and compression has been described. The algorithm is based on the mathematical means of mechanics of composite materials and in situ deformation properties of constituents. The mean field approach has been applied. The stress–strain behavior depends on such microstructural parameters as cobalt volume fraction, mean carbide grain size, and contiguity of carbide phase. The technological thermal residual microstresses have been taken into account. The wide comparison of theoretical and available experimental results has been done. It has been shown, that the given calculating algorithm has the good predictive capability. The analytical expressions of tensile and compressive strength of WC-Co hardmetals have been given.